Optimalisasi Branding Produk Rendang Biyan di Kota Payakumbuh melalui Strategi Komunikasi Pemasaran Digital dalam Rangka Meningkatkan Komersialisasi - Lita, Ratni Prima; Verinita, Verinita; Syukri, Daimon; Yuliviona, Reni; Mardiah, Fatma Poni; Khatimah, Husnul; Putri, Natasya; Dini, Kartika Cahya; Gema, Vendiro Mailevan; Safira, Alya Arsya (Jurnal Hilirisasi IPTEKS, 2025)
Payakumbuh is a city in West Sumatra province, famous for its rendang. Rendang Biyan is a small business in Payakumbuh city that produces rendang with a distinctive, authentic taste. To market its products, Rendang Biyan uses Instagram as an effort to increase sales in the digital era. However, digital content management via Instagram has not strengthened branding and has not yielded maximum results, with a limited number of followers of around 336. Rendang Biyan also does not regularly update its products on Instagram. Given the problems faced by Rendang Biyan, it is necessary to conduct community service activities there. The method used is socialization and mentoring, focusing on optimizing Rendang Biyan's Instagram content to strengthen its branding in consumers' minds. The results of the mentoring show an increase in Instagram followers and strengthened branding through additional activities and interactions with visitors and followers. Members of the Rendang Biyan group enthusiastically attended this community service activity. Following this community service activity, the number of followers increased significantly from 336 to 393 in a relatively short period. While initial results show a positive increase, there are still efforts to improve the use of user-generated content, such as photos or videos uploaded by consumers while using the product. This will be maximized in the future to enhance Rendang Biyan's performance and enable it to compete in the national market.